Constraints in Adoption of Climate Resilient Agricultural Technologies in Telangana - Naik, Boda Mahesh; Singh, A. K.; Maji, Saikat (Indian Journal of Extension Education, 2022)
The two major agrarian challenges of the modern era are climate change and food security. Unquestionably the best way to address these issues is adaptation through climate resilience. Making the nation’s most susceptible areas climate resilient is the goal of the ICAR effort known as “National Innovations in Climate Resilient Agriculture” (NICRA). Since the inception of the project, several climate resilient technologies have been demonstrated across the country. The investigation was undertaken to isolate the constraints in the adoption of these technologies in Telangana state using a sample size of 200 respondents from four villages in two districts. The findings of Garrett ranking analysis revealed that more interest to follow conventional practices, inadequate institutional financial support, inadequate services through CHCs and insufficient effort on the part of the officials to provide services to all farmers during the busiest season were the predominant constraints to the adoption of climate resilient agricultural technologies by farmers.
Keywords: Adoption; Adaptation; Climate resilience; Constraints; NICRA